The Impact of Tai Chi Exercise on Self-Efficacy, Social Support, and Empowerment in Heart Failure: Insights from a Qualitative Sub-Study from a Randomized Controlled Trial - Yeh, Gloria Y. (PLoS One, 2016)
OBJECTIVE: To qualitatively explore perceived physical and psychosocial effects and overall patient experience associated with a 12-week tai chi (TC) intervention and an education group in a clinical trial of patients with chronic heart failure (HF). SUBJECTS AND METHODS: We randomized 100 patients with chronic systolic HF (NYHA Class 1–3, ejection fraction≤40%) to a 12-week group TC program or an education control. At 12-weeks, semi-structured interviews were conducted on a random subset (n = 32; n = 17 in TC, n = 15 in control), audiorecorded and transcribed verbatim. Two independent reviewers extracted information using grounded-theory methods for emergent themes. We explored similarities and differences in themes/sub-themes between the groups, and examined qualitative association with changes from baseline to post-intervention in previously reported quantitative measures (e.g., Minnesota Living with HF, Cardiac Exercise Self Efficacy and Profile of Mood States). RESULTS: The mean age (±SD) of participants was 68±9 years, baseline ejection fraction 29±7%, and median New York Heart Association class 2 HF. We idenitifed themes related to the patient’s experience of illness, perceptions of self, and relationship to others. Specific psychosocial and physical benefits were described. Common themes emerged from both groups including: social support and self-efficacy related to activity/exercise and diet. The tai chi group, however, also exhibited a more global empowerment and perceived control. Additional themes in TC included mindfulness/self-awareness, decreased stress reactivity, and renewed social role. These themes mirrored improvements in previously reported quantitative measures (quality-of-life, self-efficacy, and mood) in TC compared to control. Patients in TC also reported physical benefits (e.g., decreased pain, improved energy, endurance, flexibility). CONCLUSION: Positive themes emerged from both groups, although there were qualitative differences in concepts of self-efficacy and perceived control between groups. Those in tai chi reported not only self efficacy and social support, but overall empowerment with additional gains such as internal locus of control, self-awareness and stress management. Future studies of mind-body exercise might further examine perceived control, self-efficacy, and locus-of-control as potential mediators of effect.